A Transversal Study of Biochemical Profile, Urinalysis, UPC, Electrolytes and Blood Pressure in Dogs with Chronic Kidney Disease - Antunes Ribeiro, Jose Francisco [UNESP]; Aquinas Liguori, Tacia Tavares; Vieira Le Sueur, Andre Nanny [UNESP]; Padovani, Carlos Roberto [UNESP]; Arruda Monteiro, Maria Jaqueline Mamprim de [UNESP]; Melchert, Alessandra [UNESP]; Chalfun Guimaraes-Okamoto, Priscylla Tatiana [UNESP] (Univ Fed Rio Grande Do Sul, 2020)
Background: Chronic kidney disease (CKD) affects both dogs and cats, mainly elderly animals, due to tubulointerstitial inflammation associated with the increase of fibrosis through the excess deposition of extracellular matrix (ECM) which leads to decrease glomerular filtration. Many different underlying renal diseases can affect the kidneys of dogs such as congenital or acquired in origin. Therefore, the main objective of this transversal study was to evaluate the epidemiology through clinical and laboratory evaluation of 225 client-owned dogs with CKD. Materials, Methods & Results: Complete blood count (CBC), urinalysis, and biochemical profile were retrospectively selected and evaluated from 225 client-owned dogs with CKD of both sexes, different ages, and breeds from the patient population of the Nephrology and Urology Small Animal Service of the Teaching Hospital of the School of Veterinary Medicine and Animal Science - Sao Paulo State University from 2011 to 2017. All dogs were divided in groups according to the International Renal Interest Society (IRIS) CKD grading and statistical analysis was performed according to Kruskal-Wallis non-parametric test complemented with Dunn's multiple comparisons test, and analysis of variance for the model with a factor complemented with the test of multiple comparisons of Tukey. In this retrospective study, we observed that most dogs in all groups were elderly (>= 9 years old). CBC demonstrated lower RBC's (P < 0.005), hemoglobin (P < 0.001), hematocrit (Ht%) [P < 0.001] at the highest stage of the disease. However, urinary specific gravity (USG) did not demonstrate significant differences between the disease stages, but urinary protein: creatinine ratio (UPC) was statistically different (P < 0.01) between IRIS-CKD stages 1 and 4. Furthermore, serum phosphate concentrations demonstrated significantly higher levels in dogs at IRI-CKD stage 4 compared with IRIS-CKD stage 3 (P < 0.001). Discussion: The analysis of 225 dogs with CKD showed that 130 animals were elderly, older than 9 years, and according to previous studies, 15% of dogs over 10 years of age are diagnosed of CKD, presenting significant morbidity and mortality. Laboratory findings such as the presence of non-regenerative anemia is expected in dogs with CKD. In our study, the degree of anemia corresponded with the stage of the disease, similarly to serum creatinine concentrations. Another important laboratory finding in diagnosing CKD is the early detection of the kidney's abilities in concentrating its tubular filtrate. In this retrospective study, isosthenuria was not significant due to all dogs presented CKD as criteria of inclusion, especially those without azotemia, although, proteinuria was reported in 90% of the population investigated. Electrolyte imbalances are also expected in CKD. However, despite serum sodium, potassium, and total calcium did not demonstrate significant results, serum phosphate had its significance between IRIS-CKD stage 3 and stage 4. Hence, despite the age factor of most dogs in all groups, with the association of laboratory results such as serum creatinine, serum phosphorus, ionized calcium, erythrogram, isosthenuria, SBP, and the degree of proteinuria, it was possible to perform early diagnosis of CKD even in dogs with IRIS-CKD Stage 1 in a stable and hydrated patient. With the proper diagnostic, staging and substaging according to IRIS guidelines, these parameters can be monitored, predicting longevity and good quality of life, or progression of the disease with a more reserved prognosis.
Keywords: chronic kidney disease; kidney; canine; azotemia